Medical students’ perception of their educational environment during foundation course - Maharjan, Shreekrishna; Shakya, Tripti (International Journal of Research in Medical Sciences, 2020)
Background: Learning environment is how students perceive the climate of an institution. The strength and weakness of learning environment should be identified to help change, adjust and manage training programs with objectives for improving learning quality. Dundee Ready Education Environment Measure (DREEM) is a validated tool designed to measure educational environment specifically for medical schools and other health profession institutions. This tool has been used in 20 countries, including Nepal. The aim of this study was to determine the perception of medical students of Foundation Course toward their learning environment using this tool. Methods: The study was conducted among the medical students attending Foundation Course in School of Medicine at Patan Academy of Health Sciences in Nepal using the DREEM tool. Results: Total mean of DREEM score was 150.51 and that of subscales for Students’ Perception of Learning (SPL), Students’ Perception of Teachers (SPT), Students’ Academic Self-Perception (SASP), Students’ Perception of Atmosphere (SPOA) and Students’ Social Self-Perception (SSSP) were 36.96/48, 34.01/44, 23.96/32, 36.03/48 and 19.55/28 respectively. In item scores, students scored more than 3 for 29 items, between 2 and 3 for 20 items and only 1 item received less than 2 score indicating an issue requiring attention on overemphasis of factual learning during the course. Conclusions: Students have a positive perception about their educational environment. Their perception is a valuable resource for institutional curriculum planners to make appropriate changes to enhance student learning. It is important to get feedbacks from students on how they are experiencing their learning environment.